Synthesis and characterization of new 1,4-dihydropyran derivatives by novel Ta-MOF nanostructures as reusable nanocatalyst with antimicrobial activity - Ahmad, Irfan; Jasim, Saade Abdalkareem; Yasin, Ghulam; Al-Qargholi, Basim; Hammid, Ali Thaeer (Frontiers in Chemistry, 2022)
Novel Ta- MOF was synthesized under mild conditions by ultrasound irradiations. The sample was characterized by SEM, FTIR, TG and BET technique. The final structures showed high physicho-chemical properties including narrow particle size distribution, homogenous morphology, high thermal stability and remarkable surface area. Ta- MOF synthesized in this study was used as a catalyst in the synthesis of 1,4-dihydropyran derivatives. The results proved that it has a high catalyst capability. Its advantages include high recyclability, less reaction time with higher efficiency and synthesis of new1,4-dihydropyran derivatives. In the following, antimicrobial activity including antifungal and antibacterial activity of Ta- MOF nanoparticles based on Minimum Inhibitory Concentration, Minimum Fungicidal Concentration and Minimum Bactericidal Concentration were also evaluated and synthesized Ta- MOF, in addition to high catalytic properties, showed high antimicrobial activity and can be introduced as an agent against bacteria and fungi.